Judicial independence and its endemic shortage of guarantees - Andrés Ibáñez, Perfecto (Journal of the Basque Parliament, 2021)
Practical experience and theoretical elaboration (always in a close conflict relationship) have contributed to the long process of historical development of the value of judicial independence. This paper briefly presents this process considering both aspects of the matter. The author also analyses critically the napoleonic model of judicial organisation, a real landmark, extraordinarily widespread and particularly negative from the point of view of judicial independence, which has left its imprint on all judicial organisations in continental Europe. The paper pays attention to the extremely significant fact of the easy functional integration of judges with this profile in the European experience of nazism and fascism. The writer also reflects on the requirements imposed by the current constitutionalism based on rights on the judicial role model and the judicial status. Finally, the paper focuses on the distressing Spanish experience concerning the General Council for the Judiciary.